PENGARUH LITERASI KEUANGAN DAN PERILAKU KEUANGAN TERHADAP KEPUTUSAN INVESTASI DI CRYPTO - Muhammad Distian Andi Hermawan (Journal of Financial Economics & Investment, 2023)
The problem that occurs is that the people of Palembang do not understand where to start investing.  This is based on the ability of a low level of financial literacy. This study aims to see the influence of financial literacy and financial behavior either partially or simultaneously. This study uses a quantitative approach where the data obtained uses questionnaires or questionnaires in the form of questions asked to respondents. Respondents is used in this study are 30 respondents. Analysis technique used linear regression. The results of this study show that Variable (X1) Financial Literacy does not have a partial influence on Variable (Y) Investment Decisions. Variable X2 Financial Behavior has a positive and significant influence on Variable (Y) Investment Decisions. The simultaneous test show that both Independent Variables (X1) Financial literacy and (X2) Financial behavior have a positive and significant influence on the Dependent Variable (Y) Investment Decision.